The Strategies of Academic Library to Serve Net-Generation - setiawan, candra pratama (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2015)
The fast developments in information and communication technology have rapidly shaped and created enormous changes in the way people live and use libraries. The generation who grow in this era is called net generation. Academic libraries, where the majority of the users are the netgeneration, have started to implement the concept of hybrid library as a response of the technological advances. The trend of digital collections usage is getting increase, on the other hand, the number of library visitor is getting lower significantly. The condition make librarians afraid of being abandoned by its users, whereas libraries still have many physical collections. This paper is written as a result of simple observation in some libraries where the needs of netgeneration has accomodated. The concept of library as place, and library marketing offer the solutions to deal with the problem. Libraries can develop and provide some facilities that suitable with the net-generation characteristics. In addition, libraries can create some events to promote their services even the collections to attract the users to visit library.Â Â Â